Race craft: A qualitative exploration of the development, implementation and reflection of tactical decision making in road cycling - O`Grady, M. W.; Worn, R.; Owens, J. O.; O`Brien, B. J.; Talpey, S. W. (International Journal of Sports Science and Coaching, 2023)
Historically, research that has aimed to understand the determinants of road cycling performance has focused primarily on the physiological characteristics of successful performers. To date, little research has been conducted on the tactical strategies that underpin successful road cycling, especially from a qualitative perspective. This study reports the practices of seven high-performing Australian cyclists and coaches to inform how they prepare for competition, the tactical decisions they make during and reflective practices they use following a road cycling competition. Inductive qualitative one-on-one semi-structured interviews were conducted using open-ended questions via an online meeting platform. A robust thematic analysis of the interviews was undertaken resulting in the establishment of themes aligned with pre-race, in-race and reflection upon tactical decision making. Prior to the race, themes related to the specificity of training, planning of a race strategy and use of training data emerged from the interviews. During the race, themes of the cyclist`s role within a team, in-race communication and race craft were established. Post-race, a theme related to the reflective practice implemented by each participant was evident. These results and discussion provide novel insights into the process of developing, implementing and reflecting upon tactical decision making used in high-level road cycling. This information is valuable for teams and governing bodies to inform and enhance coaching development and practice within the sport of road cycling.